2021
DOI: 10.1021/acsinfecdis.1c00096
|View full text |Cite
|
Sign up to set email alerts
|

Human Cathelicidin Inhibits SARS-CoV-2 Infection: Killing Two Birds with One Stone

Abstract: SARS-CoV-2 infection begins with the association of its spike 1 (S1) protein with host angiotensin-converting enzyme-2 (ACE2). Targeting the interaction between S1 and ACE2 is a practical strategy against SARS-CoV-2 infection. Herein, we show encouraging results indicating that human cathelicidin LL37 can simultaneously block viral S1 and cloak ACE2. LL37 binds to the receptor-binding domain (RBD) of S1 with high affinity (11.2 nM) and decreases subsequent recruitment of ACE2. Owing to the RBD blockade, LL37 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 56 publications
2
86
0
Order By: Relevance
“…Recent in silico molecular docking studies predicted strong binding interactions of LL-37 (Lokhande et al, 2020) and hBD-2 (Zhang L et al, 2021) with the receptor-binding domain (RBD) of SARS-CoV-2, suggesting an RBD blocking potential for these two peptides. Biophysical assays using bio-layer interferometry (BLI) and microscale thermophoresis (MST) supported the in silico findings for LL-37 (Wang C. et al, 2021) and hBD-2 (Zhang L. •Aggregates IAV and enhances neutrophil-mediated clearance [Hartshorn et al (2006), Tecle et al (2007), Doss et al (2009)] •Inhibits IAV replication through the inhibition of protein kinase C (PKC) in infected cells [Salvatore et al (2007)] HD5…”
Section: Antimicrobial Peptides As Viral Binding Inhibitors That Can Block Cov-2 Entrymentioning
confidence: 69%
See 3 more Smart Citations
“…Recent in silico molecular docking studies predicted strong binding interactions of LL-37 (Lokhande et al, 2020) and hBD-2 (Zhang L et al, 2021) with the receptor-binding domain (RBD) of SARS-CoV-2, suggesting an RBD blocking potential for these two peptides. Biophysical assays using bio-layer interferometry (BLI) and microscale thermophoresis (MST) supported the in silico findings for LL-37 (Wang C. et al, 2021) and hBD-2 (Zhang L. •Aggregates IAV and enhances neutrophil-mediated clearance [Hartshorn et al (2006), Tecle et al (2007), Doss et al (2009)] •Inhibits IAV replication through the inhibition of protein kinase C (PKC) in infected cells [Salvatore et al (2007)] HD5…”
Section: Antimicrobial Peptides As Viral Binding Inhibitors That Can Block Cov-2 Entrymentioning
confidence: 69%
“…Additionally, biochemical studies with hBD-2 showed that it inhibited the RBD from binding ACE2 and prevented S protein-expressing pseudovirions from infecting ACE2-expressing human cells (Zhang L. et al, 2021). Interestingly, LL-37 has been found to suppress S pseudovirion infection in a dose-dependent manner with an IC 50 value of 1.05 μM (Wang C. et al, 2021). By using a clever in vivo model that incorporated ACE2-expressing adenovirions, either with or without S protein-expressing pseudovirions, Wang J. et al (2021) were able to show that intranasal administration of LL-37 protected mice from pulmonary infection (Wang C. et al, 2021).…”
Section: Retrocyclinmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, human β−defensin 2 (hBD−2), an epithelial cell−derived AMP, binds to RBD with a K D of ~300 nM [ 17 ]. Human intestinal α−defensin 5 (HD−5) and LL37 can simultaneously attach both ACE2 and the Spike protein [ 18 , 19 , 20 ]. A defensin−like peptide P9R exhibited potent antiviral activity against multiple viruses including SARS−CoV−2.…”
Section: Introductionmentioning
confidence: 99%